Study on Reasonable Size of Coal and Rock Pillar in Dynamic Pressure Roadway Segment of Fully Mechanized Face in Deep Shaft - Binyang Sun; Pingsong Zhang; Haifeng Lu (Advances in Civil Engineering)
The deformation mechanism of the protective coal and rock pillar area outside a stope is an important parameter for setting a reasonable size. In this paper, based on the geological condition of working face 1231(1) in a mine in Huainan, a method that combines the use of a borehole and Brillouin optical time domain reflectometry (BOTDR) was proposed to analyze the stress variation laws of coal and rock pillar areas, and the parameters of the monitoring borehole and installation technique of the sensing optical cables were designed. Based on the monitoring data, the strain distribution characteristics of the sensing optical cables and their relationship with the rock strata were analyzed, the development law of coal and rock strata deformation during the mining process was revealed, and the transverse influence range of the coal and rock pillar affected by mining was reasonably divided. According to the results, the sensing optical cables show an overall trend of tensile strain, with a maximum value of 1800 με, and the main areas of rock strata deformation occur near the interface of rock strata. The range of rock strata disturbance along the borehole direction was approximately 38 m, and the maximum deformation of rock strata after the disturbance, namely, the displacement, was 24.87 mm. A numerical model was constructed to acquire the strain variation characteristic within 100 m in the outer floor of the working face. The transverse range of the floor disturbance was analyzed to be 30–36 m. The field test had good correspondence with the numerical simulation results, which indicates that the optical fiber testing technology can effectively describe the stress variation in the coal and rock strata. The test results can provide technical support for the rational setting of coal and rock pillars and disaster prevention and control. The research direction of deep rock mass testing is discussed, and optical fiber testing in boreholes is considered an effective method for studying deep dynamic disaster control.